MODEL PEMBERIAN PERINGKAT KINERJA PERUSAHAAN: STUDI PADA PERUSAHAAN ASURANSI JIWA DI INDONESIA - Novita Ratna Satiti (Jurnal Inovasi Ekonomi, 2019)
The purpose of this study is to provide an alternative rating company based on analysis on Profitability, RBC and Premium Expenses which are the main keys to the financial performance of Insurance Companies. This research uses the Fuzzy Tools Box approach from Matlab to see different assessment patterns. Data is collected using the documentation method of Financial Statements of Insurance Companies listed on the IDX in the last five years. The research subjects were as many as 10 insurance companies that met the criteria in Indonesia. The results showed that the first dominant insurance rating in taking insurance decisions was Lippo General Insurance, second Indonesian Reinsurance Insurance, third Multi Artha Guna insurance, fourth Ramayana insurance, fifth Harta Amana Pratama insurance, six Mitra Maparya insurance, seventh Jaya insurance Tania, the eight insurers of Bina Dana Arta, the ninth Dayin Mitra insurance, and the last rank of Bintang insurance which refers to the standard level of financial health of insurance companies. This study implies that the proposed ranking is a simpler and easier ranking alternative, but still has different benefits for decision makers.